2012
DOI: 10.1007/s10549-012-2216-0
|View full text |Cite
|
Sign up to set email alerts
|

Mammary differentiation induces expression of Tristetraprolin, a tumor suppressor AU-rich mRNA-binding protein

Abstract: Tristetraprolin (TTP) is a RNA-binding protein that inhibits the expression of pro-inflammatory cytokines and invasiveness-associated genes. TTP levels are decreased in many different cancer types and it has been proposed that this protein could be used as a prognostic factor in breast cancer. Here, using publicly available DNA microarray datasets, "serial analysis of gene expression" libraries and qRT-PCR analysis, we determined that TTP mRNA is present in normal breast cells and its levels are significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 39 publications
1
29
0
1
Order By: Relevance
“…1 Therefore, it is reasonable that cytosolic labile Zn 2+ would increase to meet the structural or functional needs of the upregulated cytosol-localized zincdependent proteins during mammary cell differentiation. Among the list of upregulated zinc-dependent genes at D day 6, we found genes which reportedly encode cytosolic proteins that play important or essential roles in cell differentiation or lactation, including the vitamin D receptor (VDR), 60 Peptidylglycine alphaamidating monooxygenase (PAM) 61 and tristetraprolin (TTP), [62][63][64] a zinc-finger mRNA-binding protein encoded by ZIP36. TTP is highly expressed in differentiated mammary cells and the lactating mammary gland.…”
Section: Discussionmentioning
confidence: 99%
“…1 Therefore, it is reasonable that cytosolic labile Zn 2+ would increase to meet the structural or functional needs of the upregulated cytosol-localized zincdependent proteins during mammary cell differentiation. Among the list of upregulated zinc-dependent genes at D day 6, we found genes which reportedly encode cytosolic proteins that play important or essential roles in cell differentiation or lactation, including the vitamin D receptor (VDR), 60 Peptidylglycine alphaamidating monooxygenase (PAM) 61 and tristetraprolin (TTP), [62][63][64] a zinc-finger mRNA-binding protein encoded by ZIP36. TTP is highly expressed in differentiated mammary cells and the lactating mammary gland.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a deguelin-like downregulation of STAT3 phosphorylation, c-Myc or Survivin expression through inhibition of EGFR, c-Met or NF-kB signaling [50], regulation of xanthine oxidoreductase expression by protein tyrosine kinase and MAP kinase cascades [51] as well as the antioxidant function of isoflavones [52] could affect the differentiation process. Compounds that facilitate the switch of HC11 cells from proliferative to lactating stage are thought to negatively impact the modulation of oncogenic signaling in breast cancer, as exemplified for instance by the inverse association of HC11 cell differentiation markers Tristetraprolin and Xanthine oxidoreductase with tumor grade [53,54]. In addition, it has been reported that treatment of HC11 cells with lactogenic hormones and of human breast cancer cells with certain chemical agents induce similar morphological and molecular traits that are characteristic of differentiated ductal epithelial cells [55].…”
Section: Discussionmentioning
confidence: 99%
“…PIM2 is a typical oncogene in many cancers, but TTP is reported as a tumor suppressor (Goddio et al, 2012;Swords et al, 2011). We therefore hypothesized that PIM2 might regulate TTP protein levels.…”
Section: Pim2 Negatively Regulates Ttp Protein Levels Through the Ubimentioning
confidence: 99%